ANALISIS PENGARUH SEKTOR PRODUKTIF TERHADAP KEMISKINAN DI KABUPATEN ACEH UTARA - Ayu Niara; Andria Zulfa (LPPM UNIMAL, 2019)
The purpose of this study was to determine the effect of the Agricultural Sector (X1) and the Processing Industry Sector (X2) on Poverty (Y) in North Aceh District. To achieve this goal this study uses secondary data in the form of time series in 2010-2016 which are sourced from the North Aceh Regency BPS. Methods of data analysis using Multiple Linear Regression. The results showed that partially stated that the previous year's poverty variable had a positive effect on poverty in North Aceh District, the agricultural sector variable had no effect and negative on poverty (Y) in North Aceh District and the processing industry sector variable had no significant and negative effect on poverty (Y) in North Aceh Regency.Taken together, the poverty variable of the previous year, Agricultural Sector variable (X1) and Processing Industry Sector (X2) had a significant effect on Poverty (Y) in North Aceh District..